Effect of Different Doses of Sugammadex on Recovery and Hemodynamic Parameters in Reversing Neuromuscular Blockade in Patients Undergoing Electroconvulsive Therapy - Kadir ARSLAN; Gozde UCUKSARAC; Hale CETIN ARSLAN; Erkan AYDIN; Ayca Sultan SAHIN (Medeniyet Medical Journal)
Objective: This retrospective observational study aimed to investigate the effect of different doses of sugammadex used in reversing neuromuscular blockade in electroconvulsive therapy (ECT) procedures on patient recovery and hemodynamic measurements. Methods: Anesthesia induction was performed using propofol (1 mg/kg) and rocuronium (0.4 mg/kg). Patients were classified into group 2 (2 mg/kg) and group 3 (3 mg/kg) according to the dose of sugammadex used to reverse neuromuscular blockade. The patient's spontaneous breathing time, eye-opening time, time to comply with voluntary commands, time to reach Modified Aldrete score (MAS) 9, complications, and hemodynamic data were analyzed. Results: In total, 314 ECT sessions were performed on 46 patients. The average age of the patients was 38.3+-12.6 years, and 56.6% (n=26) were male. While the average number of ECTs applied to the patients was 6.8+-2.8, the average seizure duration was 28.2+-12.7 seconds. The most common diagnosis (32.7%) in patients who underwent ECT was bipolar disorder. The average time to recovery of spontaneous breathing, eye-opening time, time to comply with voluntary commands, and time to reach MAS 9 were found to be significantly lower in group 3 (p<0.001, p<0.001, p<0.001, and p=0.002, respectively). Tooth damage was observed in 0.3% (n=1) and tongue abrasion in 0.6% (n=2) of the cases. Hemodynamic measurements were similar between groups (p>0.05). Conclusions: Sugammadex used at a dose of 3 mg/kg in ECT procedures significantly reduces recovery times compared with 2 mg/kg. However, both doses can be safely and cost-effectively used to reverse the neuromuscular blockade provided by 0.4 mg/kg rocuronium.